Dakwah Dan Politik Identitas: Implikasi Kehidupan Keagamaan Dalam Dinamika Sosial-Politik Kontemporer - Sukirno, Sukirno (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study examines the intersection of dakwah (Islamic preaching) and identity politics within the contemporary socio-political context of Indonesia. The research addresses the rising influence of identity politics based on religious affiliation and its impact on social cohesion and political behavior. By employing a mixed-methods approach that includes surveys and in-depth interviews with religious leaders, preachers, and community members, the study explores how dakwah functions both as a tool for political mobilization and as a potential mediator fostering social harmony. Key findings reveal that while dakwah is often co-opted to advance exclusive political agendas leading to increased polarization and social fragmentation, moderate dakwah practices promote inclusivity, tolerance, and conflict mitigation. The research highlights the strategic role of moderate dakwah in countering divisive identity politics, especially when integrated with digital media platforms, thus extending its outreach and dialogical capacity. The study concludes that maintaining the moral and spiritual integrity of dakwah requires regulatory frameworks that prevent its excessive politicization. Future research is recommended to deepen the understanding of digital media’s influence on dakwah and identity politics, as well as longitudinal studies to track their evolving dynamics in Indonesia's pluralistic society. This work contributes to scholarly discourse by proposing a context-sensitive model of dakwah that balances religious messaging with socio-political realities, aiming to support peacebuilding and democratic consolidation.